Neohyalinocerus, a new genus of Idiocerini for Amritodus flavoscutatus Cai & Shen, 1998 (Hemiptera: Cicadellidae) from China - Zhang, Bin; Yue, Yiming; Li, Guoqing; Bao, Sarina; Zhang, Hui (Zootaxa, 2026)
Neohyalinocerus Zhang gen. nov., is described to accommodate Amritodus flavoscutatus Cai & Shen, 1998, resulting in the new combination Neohyalinocerus flavoscutatus (Cai & Shen). The genus is characterized by the presence of some transverse rugae on the head and pronotum, and presence of a ventral process on the male pygofer.